Advanced breast cancer with cachexia: A case report. Issue 4 (29th January 2021) - Liu, Nan; Li, Shuting; Jia, Junmei; Qiao, Ying; Li, Yuanfei
Abstract: Rationale: Cachexia is a clinically relevant syndrome in cancer that is associated with reduced tolerance to anticancer therapy, reduced quality of life, and reduced survival rates. Cachexia is most prevalent in pancreatic, gastric, colorectal, lung, and head and neck cancers. It is rarely documented in breast cancer patients. Patient concerns: In our case report of a breast cancer patient with bone metastasis who was monitored throughout the course of her treatment, we document the development of cachexia using image analyses in relation to her metastatic burden. In the 2-year period, from April 10, 2015, to February 09, 2017, she lost 16% of her baseline weight. During this time, she was repeatedly hospitalized for chest tightness, edema of both lower limbs, numbness and pain in the left lower extremity and backache. Diagnoses: Our patient was a 46-year-old premenopausal woman when she was firstly diagnosed. Several years after surgery for invasive ductal carcinoma of the left breast, she had multiple systemic bone metastases (the thoracic spine, the ribs, etc), lung metastasis, bilateral axillary lymph node metastasis, and metastasis of the right neck lymph node in IV area. Interventions: The patient completed 6 cycles of postoperative adjuvant chemotherapy and long-term endocrine therapy after a radical mastectomy for breast cancer. During the fourth progression, 6 cycles of rescue chemotherapy were performed. Local lumbosacral radiotherapy, and lumbar surgery were carried out to relieve symptoms after several progressions. Outcomes: She became extremely thin, weighing only 50 kg at admission on July 23, 2018. This eventually led to multiple organ failure and death. Lessons: We noted a strong negative correlation between the abdominal muscle area and the metastatic tumor area at the second lumbar vertebral (L2) level. The monitoring of abdominal muscle wasting may serve as a marker, and therefore a prognostic factor, for both cachexia and the extent of metastatic disease. This is especially true with breast cancer, where metastasis to bone is frequent. Our data from a computational tomography radiological quantification, may provide clinicians with early indications of the extent of cachexia in metastatic breast cancer patients.